Pengaruh Mindfulness Dalam Meningkatkan Kompetensi Sosial Emosional, Motivasi Belajar Dan Regulasi Emosi (Amigdala) Pada Siswa Sekolah Dasar: The Effect of Mindfulness on Improving Social-Emotional Competence, Learning Motivation, and Emotional Regulation (Amygdala) in Elementary School Students - Ratu Meri Agusta; Sulthona Faturrohman; Ully Arta Miladia (Sumule Indonesia Publishing, 2025)
This study investigates mindfulness practices' influence on improving social-emotional competence, learning motivation, and emotion regulation (specifically the amygdala) in elementary school students. Through a literature review, this study analyzes various previous studies on mindfulness implementation in elementary school children. The results of the study indicate that mindfulness has significant potential in improving various aspects of child development, including social-emotional competence, learning motivation, and emotional regulation abilities. The mechanisms of mindfulness in influencing the amygdala as the centre of emotion are also discussed in this study. The implications of the findings of this study for the development of curricula and learning practices in elementary schools will be further explained.